(untitled) (Andamios, Revista de Investigación Social, 2024)
In this article, two cases of small-scale renewable energy generation are briefly analyzed, one located in Tecoh, Yucatán and another located in Punta Allen, Quintana Roo, both of the photovoltaic type but with important technical and implementation characteristics. For this reason, the text begins by describing what distributed generation consists of, isolated systems and the different regulatory frameworks and financing that encourage them. Two concepts are taken up: energy poverty (García, 2016) and energy justice (Sanz, 2019) to investigate how these projects can contribute to making access to energy more equitable.